The War on Cancer: A Military Perspective - Oronsky, Bryan; Carter, Corey A.; Mackie, Vernon; Scicinski, Jan; Oronsky, Arnold; Oronsky, Neil; Caroen, Scott; Parker, Christopher; Lybeck, Michelle; Reid, Tony (Frontiers in Oncology, 2015)
Actually it hasn’t quite happened yet, but almost imperceptibly, by degrees, we are learning to live with cancer. The “War on Cancer”, although generally successful in the pediatric population, has gradually been replaced with a kinder, gentler treatment paradigm that strives to contain and maintain with stalemate over checkmate, a strategy that may literally constitute the path to least resistance. The purpose of this review is 1) to critically examine the War on Cancer as a powerfully evocative metaphor that is directly responsible for a counterproductive and even potentially dangerous war-like cell-kill treatment paradigm 2) to suggest that a reframing of this metaphor in less retaliatory and aggressive terms along with a shift in clinical practice from a maximalist to a minimalist strategy is more appropriate to the treatment of cancer and 3) to draw on examples from the military sector as points of reference and comparison that closely parallel the three therapeutic ‘control and containment’ strategies discussed in this review: 1)‘Optimox-like’ trial designs 2) epigenetic modulation 3) metronomic dosing.